Examining equity in access to long-lasting insecticide nets and artemisinin-based combination therapy in Anambra state, Nigeria - Mbachu Chinyere O; Onwujekwe Obinna E; Uzochukwu Benjamin SC; Uchegbu Eloka; Oranuba Joseph; Ilika Amobi L (BMC, 2012)
Abstract Background In order to achieve universal health coverage, the government of Anambra State, southeast Nigeria has distributed free Long-lasting Insecticide treated Nets (LLINs) to the general population and delivered free Artemisinin-based Combination Therapy (ACT) to pregnant women and children less than 5 years. However, the levels of coverage with LLINS and ACTs is not clear, especially coverage of different socio-economic status (SES) population groups. This study was carried out to determine the level of coverage and access to LLINs and ACTs amongst different SES groups. Methods A questionnaire was used to collect data from randomly selected households in 19 local government areas of the State. Selected households had a pregnant woman and/or a child less than 5 years. The lot quality assurance sampling (LQAS) methodology was used in sampling. The questionnaire explored the availability and utilization of LLINs and ACTs from 2394 households. An asset-based SES index was used to examine the level of access of LLINS and ACTs to different SES quintiles. Results It was found that 80.5 % of the households had an LLIN and 64.4 % of the households stated that they actually used the nets the previous night. The findings showed that 42.3 % of pregnant women who had fever within the past month received ACTs, while 37.5 % of children ≪5 years old who had malaria in the past month had received ACTs. There was equity in ownership of nets for the range 1-5 nets per household. No significant SES difference was found in use of ACTs for treatment of malaria in children under five years old and in pregnant women. Conclusions The free distribution of LLINs and ACTs increased household coverage of both malaria control interventions and bridged the equity gap in access to them among the most vulnerable groups.